Socio-Economic Analysis And Education Level of the Community in Bukit Malintang Village, Sungai Aur Subdistrict, West Pasaman Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Study This aim know description condition social economics and description level education in Bukit Malintang Village , Sungai Aur District , District West Pasaman in West Sumatra Province . Analysis is done using secondary data and surveys field . Research _ This use approach descriptive qualitative Study This focus analysis on conditions social and economic public Bukit Malintang Village which includes amount population , number of households, background behind ethnicity , religion, interaction social , age , level education , income , and employment ( eyes livelihood ). explain existing phenomenon _ with give description in a manner clear and appropriate with facts on the ground in detail later served in form map , As for the method data collection , namely primary data and secondary data , which was carried out with method survey right on location research and obtained through Bappeda . As for the results analysis performed _ in Bukit Malintang Village The nationality of the Aur River is village resident transmigrants _ originate from The majority of Lolo intersections resident dominant is ethnic group mandailing and a small portion ethnic group java . Livelihoods are dominated by farmers _ garden palm with with percentage of 57.5 %, as farmer besides palm ie paddy fields or fields by 35%, percentage resident as civil servants 5% and residents as head elementary school 2.5%. Resident own income per month with amount Rp . 2,000,000, - the most dominating with percentage of 57.5%. Group working age and as _ head the average family is dominated in the group aged 45-49 years with percentage of 57.5%. At the average education level of the population in Bukit Malintang Village is school elementary (SD) with the percentage is 62.5% and the education level of children in Bukit Malintang Village is also at the highest level Elementary School (SD) but already 17.07% of the population has children Already up to Undergraduate Education (S1). Keywords: Condition Social , Economic, Education, Village transmigrants